Triskelionia, a new African genus of the Celaenorrhinini (Lepidoptera: Hesperiidae) and the promotion of T. compacta to species-status. - Llarsen, Torben B.; Congdon, T. Colin E. (Zootaxa, 2011)
Triskelionia is defined and described as a new genus for the Afrotropical skipper known as Sarangesa tricerata (Mabille, 1891) (Hesperiidae, Pyrginae, Celaenorrhinini). Its subspecies S. tricerata compacta Evans, 1937 is raised to species rank. The host plant is Dalbergia armata (Fabaceae) and it is the only known member of the African Celaenorrhinini that does not have Acanthaceae as host-plant and the pupa is the only one known without a free proboscis sheath.